A Study of Behavioural and Emotional Problems in School Going Indian Adolescents: The Impact of Changing Socio-Cultural and Economic Factors on Mental Health in Indian Adolescents (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In the present century, the socio-cultural, economic paradigm is fast changing owing to globalisation, and rapid advances in technology. The and intensity of our socio-economic growth has made life fast, dynamic and competitive. Today's children are not under the influence of this radical transition. Which has accelerated pressures on kids for their effective preparation to keep pace with global societies demanding that children and youth face a mental health crisis. This eventually influences their university performance, because mental wellbeing and well-being are a requirement for academic success and since issues of mental health are an obstacle to children's learning. The important components of a society's human resources are children and youth. This is the beginning of the chance portal and the stage for a stable and prosperous adult life. A balanced mental wellbeing is also a foundation for the stable growth of maturity and later lives. Thus children's mental health is an integral component of development and progress. Adolescence, the second decade of existence (10-19 years) is a vital step in the course of human evolution from infancy to adulthood. The school children are now undergoing a significant physical, behavioural, psychological, mental, and attitude transformation with changing social contact habits, perceptions, and relationships. Adolescence is a time of rapid transition in all growth aspects that requires continuous adaptation to the changing phase of development. In general, these causes cause new tension and affected mental and behavioural disorders and issues in their lives. According to UNICEF, the world's demographic was projected at 1.2 billion youth in 2009, making up about 18 of the world's population. The population of India's adolescents is 253,2 million according to the 2011 census, which makes up 20 of the Indian population.